Measuring the level of mental health among Basra University students - Ameera Abdul Kareem Marran Al-Marie ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The current study aimed to measure the level of mental health among Basra University students, and the difference between males and females with their general mental health level,  and to identify the most common mental disorders among them and the extent of their prevalence in comparison to other disorders and a measure of their mental health level, And for this purpose the researcher chose a sample consisting of (225) male and female students from the fourth stage of the students of the College of Administration and Economy and the College of Education for Girls and scientific and human specialties from the accounting, financial and banking sciences and the Department of Educational and Psychological Sciences respectively, and the researcher used the modified mental health scale consisting of (90) paragraphs after extracting truth and persistence to it The result resulted in an acceptable level of mental health among the research sample, and there are statistically significant differences at the level of significance (0.05) for the benefit of females, and the depression disorder came first, followed by obsessive-compulsive disorder and physical symptoms in the second and third ranks respectively, and anxiety ranked fourth Among the most common disorders, the results were then discussed and interpreted in light of the results of the current research, compared to the results of the study. In the previous days, a number of recommendations and proposals for concern with mental health reduced in accordance with mental health approaches and standards.